The monument of Heine on Town Hall Market in Hamburg - Köster, Udo (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
Based on the documents of the Hamburg Denkmalschutzamt (Monument Protection Office), the article retraces the political process between 1956 and 1982, which led to the erection of a Heinrich-Heine-Statue on the Rathausmarkt (Town Hall Market).